2020
DOI: 10.1088/2040-8986/abc1c6
|View full text |Cite
|
Sign up to set email alerts
|

Modulating extraordinary terahertz transmissions in multilayer plasmonic metasurfaces

Abstract: Manipulations of light–matter interaction via sub-wavelength plasmonic structures have opened up many new research opportunities in photonics from microwave to the visible spectrum, including the relatively underdeveloped but technologically important terahertz regime. Here, we have studied manipulation of terahertz transmission through a bilayer metasurface consisting of a metallic hole array and a complimentary patch array separated by an ultra-thin dielectric spacer. The terahertz transmission spectra throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…This process clearly reveals how the electromagnetic wave couples into the particle and radiates to the far field. 37 Therefore, silicon particles can be used as strong magnetic dipole resonators to enhance transmission.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This process clearly reveals how the electromagnetic wave couples into the particle and radiates to the far field. 37 Therefore, silicon particles can be used as strong magnetic dipole resonators to enhance transmission.…”
Section: Resultsmentioning
confidence: 99%
“…The process described above leads to an effective increase in the net capacitance of the structure, which shis the resonance peak progressively to the lower side of the frequency spectrum. 37,40,41 It is clearly shown that the Mie resonance structure can be dynamically and continuously modulated using the parameters of dielectric particles.…”
Section: Resultsmentioning
confidence: 99%
“…This scheme enhances the transmission through the aperture but the tuning of resonance frequency could not be realized by using the metamaterial. Recently, in another work, a bilayer structure consisting of metallic hole array and complementary metamaterial patch array was also demonstrated to manipulate the transmissions through the subwavelength hole arrays (Banerjee et al, 2020). Although this study could demonstrate significant tuning in resonance intensity, tuning of resonance frequency was bare minimum.…”
Section: Introductionmentioning
confidence: 80%
“…Fabrication of samples is done on a highly resistive silicon substrate (resistivity > 5000 Ω cm) having a thickness ∼500 μm. First, a positive photoresist is deposited on the polished side of a cleaned silicon wafer ( 100 orientation) with the help of spin coating process [54]. Then, the periodic array of the metasurface is patterned on the photoresist by means of the UV photolithography followed by a development process.…”
Section: Methodsmentioning
confidence: 99%